Penerapan Konsep Smart City dalam Aplikasi Visiting Jogja Berdasarkan Perspektif Komunikasi Lasswell - Pangestu, Dita Idfi; Atmojo, Muhammad Eko (PERSPEKTIF, 2024)
This research aims to determine how the smart city concept in the Visiting Jogja application is seen from Lasswell's communication theory. Advances in information technology mean that the government strives to improve the quality of public services provided to the community. The Yogyakarta Special Region Tourism Office is one of the agencies adopting smart cities to increase efficiency and effectiveness in delivering information services about tourism. The Yogyakarta Special Region Tourism Office launched the Visiting Jogja application because it is considered a medium easily accessible to its users. The features in the Visiting Jogja application are designed to be simple but make it easier for users to access information. This research uses qualitative research methods, with data collection techniques in the form of interviews and observations. The results of the research that has been carried out show that the Visiting Jogja application as a communicator has conveyed information about tourism in Yogyakarta effectively and informatively. Tourists, as communicants, provide feedback in the form of increased visits to all Yogyakarta tourist destinations. Thus, the Visiting Jogja application conveys information to users/tourists in an informative manner because the information conveyed is clear and easy to understand.